Oso pardo, oso pardo, qu ves ah? - Martin, Bill, 1916-; Carle, Eric; Mlawer, Teresa (New York : H. Holt, 1998)
In a question and answer game, a teacher and her group see a variety of animals, each one a different color.
Booklist
School Library Journal
3-6.
P-1.
Keywords: Color -- Fiction; Animals -- Fiction; Spanish language materials